2003
DOI: 10.1093/jn/133.11.3643
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations of (n-3) Highly Unsaturated Fatty Acids Are Good Biomarkers of Relative Dietary Fatty Acid Intakes: A Cross-Sectional Study

Abstract: A cross-sectional study was conducted to clarify the associations of lifestyle factors (habitual exercise, alcohol intake and smoking habit) and plasma fatty acid (FA) concentrations as biomarkers of dietary FA intakes. We collected 7-d weighed diet records, lifestyle information and blood samples from 15 male and 79 female Japanese dietitians, and estimated dietary FA intakes and analyzed plasma FA concentrations. Plasma concentrations of eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA) and (n-3) highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
114
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 123 publications
(137 citation statements)
references
References 47 publications
19
114
4
Order By: Relevance
“…The mean n-6 and n-3 PUFA percentages in plasma lipids are influenced by the mean intake of the population studied. Thus, the plasma level of a-linolenic acid in our sample (0.5-0.6%) is lower than that found in Japan (0.8-0.9%) (Kuriki et al, 2002(Kuriki et al, , 2003 or in United Kingdom (1.3-1.4%) (Rosell et al, 2005), reflecting the low a-linolenic acid intake of the French population (Astorg et al, 2004). At variance, the plasma linoleic acid levels reach values (30-35% of fatty acids) comparable to those found in United Kingdom (Rosell et al, 2005), Norway (Andersen et al, 1999), Japan (Kuriki et al, 2002(Kuriki et al, , 2003 or Costa-Rica (Kuriki et al, 2003;Baylin et al, 2005), reflecting the high intakes of linoleic acid in most world countries (4-6% of energy) (Simopoulos, 2002).…”
Section: Discussioncontrasting
confidence: 83%
See 4 more Smart Citations
“…The mean n-6 and n-3 PUFA percentages in plasma lipids are influenced by the mean intake of the population studied. Thus, the plasma level of a-linolenic acid in our sample (0.5-0.6%) is lower than that found in Japan (0.8-0.9%) (Kuriki et al, 2002(Kuriki et al, , 2003 or in United Kingdom (1.3-1.4%) (Rosell et al, 2005), reflecting the low a-linolenic acid intake of the French population (Astorg et al, 2004). At variance, the plasma linoleic acid levels reach values (30-35% of fatty acids) comparable to those found in United Kingdom (Rosell et al, 2005), Norway (Andersen et al, 1999), Japan (Kuriki et al, 2002(Kuriki et al, , 2003 or Costa-Rica (Kuriki et al, 2003;Baylin et al, 2005), reflecting the high intakes of linoleic acid in most world countries (4-6% of energy) (Simopoulos, 2002).…”
Section: Discussioncontrasting
confidence: 83%
“…Thus, the plasma level of a-linolenic acid in our sample (0.5-0.6%) is lower than that found in Japan (0.8-0.9%) (Kuriki et al, 2002(Kuriki et al, , 2003 or in United Kingdom (1.3-1.4%) (Rosell et al, 2005), reflecting the low a-linolenic acid intake of the French population (Astorg et al, 2004). At variance, the plasma linoleic acid levels reach values (30-35% of fatty acids) comparable to those found in United Kingdom (Rosell et al, 2005), Norway (Andersen et al, 1999), Japan (Kuriki et al, 2002(Kuriki et al, , 2003 or Costa-Rica (Kuriki et al, 2003;Baylin et al, 2005), reflecting the high intakes of linoleic acid in most world countries (4-6% of energy) (Simopoulos, 2002). Plasma levels of long-chain n-3 PUFA in our sample are much higher than in populations eating no or little fish (Baylin et al, 2005;Rosell et al, 2005), similar to those found in Norway (Andersen et al, 1999), and lower than those found in countries with a high fish consumption such as Spain (Amiano et al, 2001) or Japan (Kuriki et al, 2002(Kuriki et al, , 2003.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations